KEWASPADAAN BENCANA PADA WARGA SUKU DAYAK DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Ashari, Beny Dwi; Hariyono, Widodo (Pendidikan Geografi, 2014)
Abstract : Background: Merapi Volcano is located between Central Java and Yogyakarta Special Region (DIY), considered the most active volcanoes in the world and the intensity of the eruptions tend to be short between 3-7 years. The Island of Borneo, an area for the native Dayak tribesmen, known not pick volcanoes and plate tectonics Earth line. Residents "Dayak" need to know that there are differences in the characteristics of the disaster in Yogyakarta Special Region and the island of Borneo, and to learn and to adapt from the state. The purpose of this study to determine the citizen disaster preparedness "Dayak" in the DIY. Methods: This research uses descriptive qualitative method, which is to describe the disaster preparedness in Dayak tribesmen in the province of DIY, which consists of a description of the difference of potential disaster, the view on the citizens "Dayak" against disasters and security threats of disasters, preparedness, experiences and events trauma caused by natural disasters in the disaster in DIY. Data was collected by observation, interview and documentation. Result: Based on geography, geology, hydrology, and demographic, DIY has a condition that allows disasters (natural, non-natural, and human). Yogyakarta Special Region himself long enough until now has good title to continue their education, not to mention followed by Dayak tribesmen. By the respondents answered all of the characteristics of the narrow scope of the disaster. Yogyakarta Special Region disasters in view of relatively safe. Knowing the signs of a disaster there are lessons that never obtained before and some are aware of social media. Conclusion: Overview of the potential difference between DIY disasters with local residents origin "Dayak" different sources always vigilant and careful, there are misgivings and always alert, sources in the face of a disaster in the province is one accepted (resigned), mediocre, confused, frightened, safe, and there are gearing up to take instructions from the government through electronic media as well as the direction of the surrounding community, and the trauma experienced by interviewees tend to be brief and mild.   Keywords: disaster awareness, Dayak People, Yogyakarta Special Region.